(3efGbH CejQ GdeDefjf YeQ Hf GdNWGH (B/s - (3GHf GdLhRj, YHO GdQMef Hf Ydj Hf eMeO,s 508-597 (3g`(B.s; (3GdQTjOj , Mdej Hf GSeGYjd s ((3eUQ (B:s (3OGQ GdYbjOI ,s, 2000)
(3Ef YeQ Hf GdNWGH QVj Gddg Yfg cGf CeI aj QLd, CYR Gddg Hg GdESdGe hfUQ Hg GdeSdejf, hQaY cdeI GdJhMjO YGdjI NaGbI aj GdUOhQ, aYdi jOjg aJMJ GdHdGO, heUQJ GdCeUGQ hNVYJ ddeSdejf Cee PhGJ eOfjGJ bOjeI cGdaQS hGdQhe(B.s
(3HHjdhLQGajI (B: (3U(B. 253-254.s
Keywords: (3YeQ Hf GdNWGH Hf fajd GdbQTj,s -- 40 (3b(B. (3g`(B-23 (3g`(B.s; (3GdNdaGA GdQGTOhfs -- (3JQGLes; (3GdUMGHI hGdJGHYhfs -- (3JQGLes